Domestic savings in sub-Saharan Africa: The case of Ghana - Charles Ackah; Monica Lambon-Quayefio (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
One essential condition of economic progress in any society is an ample supply of savings, which depends on the growth of real capital. Economists agree that higher investment rates will lead to higher growth. Thus, domestic savings is considered an important determinant of growth in developing countries. However, Ghana has one of the poorest savings performances in the world. There are many reasons for the low savings rates in Ghana. In view of Ghana's aspiration to wean herself 'Beyond Aid', this study aims to provide an understanding of the longrun relationship between variables considered to be important determinant savings in Ghana. We employ time series analyses using data from 1980-2020 to capture the effects of the major policy changes in the financial sector of the history of the country, which are also likely to have implications for private savings. While the empirical analyses provide no compelling evidence of a long-run relationship between private savings and the variables considered, estimates from the short-run analysis suggest that per capita income and money supply have a significant positive relationship with domestic savings. This finding is particularly instructive because it suggests that policy makers must think critically about the kinds of policies and reforms required to boost domestic resource mobilization in the long term.
Keywords: E21; E44; E52; 330; domestic savings; financial reforms; time series; Ghana; developing countries